Reservoir Characterization of Mid Main Carbonate (MMC)interval in Cipadati Field (North West Java Basin, Indonesia) to Support Detailed Reservoir Zonation - Winardi, Sarju (2013)
Generally the MMC is known as a carbonate build up interval in the North West Java Basin, Indonesia, which contains hydrocarbons in some fields such as Rengasdengklok and North Cilamaya. In the Cipadati Field the MMC was drilled by the Explo#1 well and had a thickness of 79 meters. Previously the MMC was assumed to be a homogeneous carbonate reservoir, so petrophysical values gained from the Explo#1 well were used as default values along the entire interval. Further characterization of the MMC is needed to gain a deeper understanding of the heterogeneity of the reservoir including depositional stages, geometry, vertical facies changes, secondary pore types and porosity value. These parameters provided petrophysicists with the information necessary to divide the MMC reservoir into more detailed reservoir zones.